Acute toxicity of 2-(5-(adamantane-1-yl)-4R-1,2,4-triazole-3-ylthio) of the acetic acids and their salts' derivatives - V. M. Odyntsova; O. I. Panasenko; Ye. H. Knysh (Zaporozhye State Medical University, 2015)
Aim. To study the acute toxicity of 2-(5-(adamantane-1-yl)-4R-1,2,4-triazole-3-ylthio) acetic acids and their salts' derivatives. Methods and results. According to the data the acute toxicity of investigated substances belongs to the 4th class of toxicity and they are low-toxic, their LD50 ranges from 306 to 1520 mg/kg. The most toxic compound among the investigated compounds is derived thioacetic acid containing N4 nitrogen atom of the methyl substitute and its medium lethal dose (LD50) is 306 mg/kg. It is indicated that among the studied derived thioacetic acids and their salts' derivatives the least toxic is also derived thioacetic acid containing instead of N4 nitrogen atom phenyl radical, and its LD50 is 1520 mg/kg. After analyzing the data obtained by experimental studies of acute toxicity and chemical structure of the investigated compounds some patterns concerning the chemical structure and acute toxicity have been established. Conclusion. In the row of derived thioacetic acids from № 9 to № 1 and № 3 their toxicity increased in this case the loss of phenyl substitute of the acid 9 accompanied by a insignificant increase of toxicity, where the substitution of this phenyl substitute on the methyl leads to a significant toxicity's increase on 1214 mg/kg and is 306 mg/kg unlike 1520 mg/kg.